2013
DOI: 10.1016/j.bbrc.2013.09.064
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric packaging of polymerases within vesicular stomatitis virus

Abstract: Vesicular stomatitis virus (VSV) is a prototypic negative sense single-stranded RNA virus. The bullet-shape appearance of the virion results from tightly wound helical turns of the nucleoprotein encapsidated RNA template (N-RNA) around a central cavity. Transcription and replication require polymerase complexes, which include a catalytic subunit L and a template-binding subunit P. L and P are inferred to be in the cavity, however lacking direct observation, their exact position has remained unclear. Using supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…It is therefore not surprising that the abundance of P per particle can vary. An earlier study using a virus with a fluorescent L or P suggested that a variable amount of both of these proteins is packaged into single particles (40). The fluorescent M fusions result in viruses that are attenuated with regard to their growth, which may reflect the fact that the presence of the fluorophore itself influences the packaging of M.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore not surprising that the abundance of P per particle can vary. An earlier study using a virus with a fluorescent L or P suggested that a variable amount of both of these proteins is packaged into single particles (40). The fluorescent M fusions result in viruses that are attenuated with regard to their growth, which may reflect the fact that the presence of the fluorophore itself influences the packaging of M.…”
Section: Discussionmentioning
confidence: 99%
“…Both GSD and SIM indicate that the M matrix protein is more closely associated with the ribonucleoprotein complex (RNP) containing the RNA genome than with the virus envelope. A similar assessment of the sub-virion localization of the polymerase complex subunits, L and P, in the vesicular stomatitis virus (VSV) [83] indicated the proteins were located toward one end of the asymmetrically shaped virus and occupied ~50 nm of a 150 nm cavity inside the virion.…”
Section: Subviral Structure Localizationmentioning
confidence: 99%
“…While the beads retained their height during the AFM scan, the VSV virion has a significantly smaller young's modulus and is significantly deformed in height. In this image the virion was specifically imaged with a stiff cantilever in tapping mode which produced a small xy convolution (used to determine the tip vs blunt end of the virus) and the height difference between the tip and blunt end of the virus is used to detect extra protein density at the blunt end of the virus 19 . …”
Section: Single Virion Super Resolution Imagingmentioning
confidence: 99%
“…The aim has been to deform the virus to the point that the extra protein density within the virus becomes visible as a bump within the AFM image. This method is used to detect the extra protein density within the virus cavity 19 .…”
Section: B In Solution Antibody Attackmentioning
confidence: 99%